Mora biti dober državljan tudi zdrav? - Kamin, Tanja (Javnost (Ljubljana), 2004)
The article reflects on the power of risk communication interventions, by which public health authorities aim to regulate the population's health. According to the medical model, which is the prevailing approach in Slovenia'spublic health promotion, healthy behaviour occurs in accordance withpeople's knowledge of a healthy way of life and health risks. This relation is far from linear, however. Many factors prevent people from engaging in recommended, preventive behaviours. The article illuminates some of these factors with the help of a qualitative, empirical study of food-related concerns in Slovenia and introduces seven main categories of lay risk prevention relativisation: laborious and unhealthy discipline; corrupt and mistaken science; all-inclusive, unavoidable risk; primacy of male taste; body wisdom; optimistic bias; and expensive health management.
Keywords: zdravje; vrednote; promocija; Promotion; tveganje; način življenja; javno zdravstvo; zdravstvena politika; zdravstvena kultura